Seed quality of lablab bean (Lablab purpureus) as influenced by seed maturity and drying methods - Hanapiah, Nurul Fatin Hanani; Sinniah, Uma Rani; Mohammad Yusoff, Martini (MDPI, 2022)
The lablab bean or ‘Kacang sepat’ is a food crop originating from India and is commonly found in tropical areas such as Indonesia, Thailand and the Philippines due to its adaptability. However, in Malaysia, lablab is grown as a backyard crop, and the area cultivated with this crop is still limited. Lablab has the potential to become a commercial vegetable crop in Malaysia due to its high protein content (18–25%). Therefore, to increase lablab cultivation, good quality seeds are a prerequisite. A key factor in the production of quality seeds is the ideal harvest time of the pods during seed development and maturation and based on identifiable characteristics. The first part of this study was conducted to assess the physical characteristics of lablab pods and seeds of the cultivar Highworth (MDI 12842). Plants were grown using standard cultural practices. Pods and seeds were collected at ten different maturity stages (5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 days after anthesis (DAA)). Pods and seeds showed a significant difference in size and colour at different maturity stages. Seeds harvested at 20 DAA had maximum pod and seed size. The seeds attained physiological maturity (PM) at 30 DAA when the pod colour is light reddish brown and, after being subjected to sun and oven drying, gave maximum germination percentages of 89% and 91%, respectively, while fresh seeds had only 78% germination. Results indicated that the germination percentage of lablab improved, regardless of the drying method used. Therefore, the lablab bean pod colour is a suitable indicator to be used as an easy method for the identification of the best time for pod harvesting for seed production.